Adaptive Sliding Mode Control of a Boost Converter With Unknown Constant Power Load - David A. Zambrano-Prada; Abdelali El Aroudi; Oswaldo Lopez-Santos; Luis Vazquez-Seisdedos; Luis Marti-Nez-Salamero (IEEE Access)
In this paper, output voltage regulation in a boost converter with constant power load (CPL) is carried out by means of sliding-mode control (SMC) with an estimation loop of the output power. The estimation procedure is based on the integral of an odd-symmetric function of the output voltage error, which confers an adaptive nature to the switching regulator. Rational, trigonometric, sigmoid and $\mathop {sign}\nolimits $ -type odd-symmetric functions are analyzed to select the best candidate for output power estimation. In addition, a two-degree polynomial surface is considered to induce the sliding motions. Subsequently, the corresponding conditions for the existence of the sliding mode and for the stability of the equilibrium point including the estimation dynamics are derived. One of the main features of this proposal is that the resulting controller can be implemented analogically, requiring operational amplifier-based circuits plus a divider. PSIM $^{\unicode {0x00A9}} $ and MATLAB $^{\unicode {0x00A9}} $ simulations show a fast recovery in response to large-signal disturbances in the load power and zero steady-state output voltage error. Experimental results obtained from a 500 W prototype are in perfect agreement with both theoretical predictions and numerical simulations.